Factors Affecting Job Performance with Training as Moderation - Setia Tjahyanti (Business and Entrepreneurial Review, 2025)
This research aims to analyze the influence of Selection, Participation, and Employee Empowerment on Job Performance with Training as a moderating variable at PT Cahaya Modern Metal Industri. The object of this research is PT. Cahaya Modern Metal Industry. The form of this research is causal and descriptive. The total population was 301 employees, covering the operations and finance divisions, and the sample used was 172 employees from the operational division. This research uses a purposive sampling technique. Data was collected using a questionnaire and analyzed using SEM-PLS. Based on the results of analysis and hypothesis testing, this research shows that Selection has a significant and positive effect on Job Performance, Participation has a significant and positive effect on Job Performance, and Employee Empowerment has no significant and negative effect on Job Performance. Training has a negative moderating effect on the Selection variable on Job Performance and the Participation variable on Job Performance. Training has a positive moderating effect on the Employee Empowerment variable and Job Performance.